A199 SEVERE COLITIS FOLLOWING PELVIC RADIOTHERAPY: CASE REPORT AND REVIEW OF THE LITERATURE. (4th March 2021) - Gozdzik, M; Murthy, S
Abstract: Background: Mild-to-moderate proctocolitis is a well-known complication of pelvic radiation therapy, occurring in 43% and 6% of patients following external beam radiotherapy (EBRT) and brachytherapy (BT), respectively. This typically presents as recurrent painless rectal bleeding, diarrhea, urgency, and/or iron-deficiency anemia. Severe ulcerating proctocolitis is a less common complication of pelvic radiotherapy and is rare following BT. We report two cases of severe ulcerating proctocolitis mimicking inflammatory bowel disease (IBD) following pelvic radiotherapy in patients without known IBD, including an elderly male undergoing EBRT, and an elderly female undergoing vaginal vault BT. Aims: To describe two cases of severe ulcerating proctocolitis, mimicking IBD, following pelvic radiotherapy. Methods: Case descriptions and literature review. Results: A 71-year-old male without antecedent gastrointestinal disease developed bloody diarrhea 3 months following EBRT for treatment of prostate cancer. Infectious work-up was negative. Blood work showed anemia and an elevated CRP. CT scan showed distal large bowel inflammation concerning for proctocolitis. Flexible sigmoidoscopy revealed severe proctosigmoiditis with circumferential thickening and nodularity of the mucosa and multiple ulcers. Biopsies showed ulcer tissue with fibrinopurulent exudate. He was treated with systemic corticosteroids and symptoms gradually resolved. Repeat colonoscopy 8 months later showed healed inflammation with scarring and residual radiation proctosigmoiditis. A 74-year-old female without antecedent gastrointestinal disease developed watery diarrhea 2 weeks after initiating low dose vaginal vault BT for treatment of endometrial cancer. Infectious work-up was negative. Blood work showed an elevated CRP and CT scan revealed proctocolitis extending to the descending colon. Flexible sigmoidoscopy revealed severe ulcerating proctosigmoiditis with tram tracks of denuded mucosa. Biopsies showed moderate diffuse chronic active colitis with crypt abscesses and apoptotic bodies. She was treated with systemic corticosteroids followed by infliximab and methotrexate, with mild symptomatic improvement. However, repeat endoscopy revealed persistent severe ulceration. Unfortunately, she developed a sigmoid perforation with pelvic abscess, leading to bacteremia and fungemia, and subsequently passed. Conclusions: While rare, severe ulcerating proctocolitis mimicking IBD can occur following pelvic radiotherapy, including BT. The decision to manage these patients as IBD using immunosuppressive therapy should be weighed against the risks of these therapies, considering a patient's age and underlying health, and in collaboration with a patient's health care team. Careful assessment for risk factors and pathological findings from biopsy specimens may help in predicting the likelihood of IBD in such patients. Funding Agencies: None